2020
DOI: 10.1002/cctc.202001526
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Alkenylation of Arenes Using Supported Rh Materials: Evidence that Active Catalysts are Formed by Rh Leaching

Abstract: This work focuses on the synthesis of supported Rh materials and study of their efficacy as pre‐catalysts for the oxidative alkenylation of arenes. Rhodium particles supported on silica (Rh/SiO2; ∼3.6 wt% Rh) and on nitrogen‐doped carbon (Rh/NC; ∼1.0 wt% Rh) are synthesized and tested. Heating mixtures of Rh/SiO2 or Rh/NC with benzene and ethylene or α‐olefins and CuX2 {X=OPiv (trimethylacetate) or OHex (2‐ethyl hexanoate)} to 150 °C results in the production of alkenyl arenes. When using Rh/SiO2 or Rh/NC as c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…At 150 °C in the presence of 60 psig of ethylene and Cu­(OPiv) 2 , a TOF of 3.4 × 10 –2 s –1 (after 1 h) for styrene production using Pd­(OAc) 2 was determined. A TOF with similar magnitude (1.8 × 10 –2 s –1 ) was observed using [Rh­(η 2 -C 2 H 4 ) 2 (μ-OAc)] 2 as the catalyst precursor at 150 °C in the presence of 40 psig of ethylene and Cu­(OPiv) 2 as the oxidant . Thermolysis of Pd­(OAc) 2 in benzene in the absence of copper­(II) generates free acetic acid and Pd(0) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At 150 °C in the presence of 60 psig of ethylene and Cu­(OPiv) 2 , a TOF of 3.4 × 10 –2 s –1 (after 1 h) for styrene production using Pd­(OAc) 2 was determined. A TOF with similar magnitude (1.8 × 10 –2 s –1 ) was observed using [Rh­(η 2 -C 2 H 4 ) 2 (μ-OAc)] 2 as the catalyst precursor at 150 °C in the presence of 40 psig of ethylene and Cu­(OPiv) 2 as the oxidant . Thermolysis of Pd­(OAc) 2 in benzene in the absence of copper­(II) generates free acetic acid and Pd(0) .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we have demonstrated that Pd­(OAc) 2 affords >2400 TOs of styrene after 24 h at 150 °C. Under some conditions, the formation of elemental Rh(0) or Pd(0) does not result in catalyst deactivation, since reoxidation to soluble molecular catalysts is feasible. ,, In contrast, experiments with soluble Pt complexes are consistent with irreversible catalyst decomposition when Pt(0) is formed (Scheme ). (3) Pt­(II)-catalyzed ethylene hydrophenylation generates substantial diethylbenzenes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular complexes based on Ru, Pd, Ni, , Ir, and Pt have been reported to catalyze olefin hydroarylation (to produce alkyl arenes) and oxidative olefin hydroarylation (to produce alkenyl arenes) using unactivated arenes and olefins. Our group and others have reported Rh catalyzed aromatic C–H activation and arene alkenylation using hydrocarbon substrates, , and we recently demonstrated oxidative olefin hydroarylation using [(η 2 -C 2 H 4 ) 2 Rh­(μ-OAc)] 2 ( 1 ) as the catalyst precursor. , These reactions incorporate the Rh catalyst precursor, arene, olefin and CuX 2 (X = carboxylate such as acetate, pivalate and 2-ethylhexanoate) and are generally heated between 150 and 165 °C. Potential advantages of the Rh-catalyzed alkenyl arene formation include: (a) selectivity for linear 1-aryl alkenes (>8:1 linear/branched ratio in most cases); (b) broad substrate scope including electron-deficient arenes; (c) under some reaction conditions, quantitative yield based on Cu­(II) oxidants as the limiting reagent; and (d) aerobic oxidation by recycling Cu­(II) with air, either during catalysis or in a step separate from catalysis.…”
Section: Introductionmentioning
confidence: 99%